(3LOhi GddLhA Gdi GdJMcje GdJLGQj GdOhdjs - (3gTGe(B, (3NGdOs ((3GdGScfOQjI(B:s (3efTCI GdeYGa(B,s, 2005)
(3eRGjG GdJMcje GdJLGQj GdOhdj, QZHI GdNUhe aj JMSjf SjQ GdYOGdI, QZHI GdNUhe aj GdMUhd Ydi YOGdI eNJdaI Yf Jdc GdJj JYWjgG GdeMGce, QZHI GdNUhe aj Cf jchf GdJMcje PG WHjYI JhajbjI, QZHI GdNUhe aj MSe efGRYGJ JNQL Yf hdGjI GdeMGce, CeQGV GdJMcje GdJLGQj GdOhdj, CeQGV GdJMcje GdJLGQj GdOhdj hShA eeKdj GdOhd GdfGejI heSJTGQjgG CeGe eMGce GdJMcje GdOhdjI, CeQGV GdJMcje GdJLGQj GdOhdj heSdc HYV GdLgGJ aj HYV GdOhd (B((3eUQ(B).s
(3eQGLY U(B.625s
Keywords: (3GdJLGQIs; (3GdJMcje GdOhdjs